Reinforcement of macroscopic carbon nanotube structures by polymer intercalation: The role of polymer molecular weight and chain conformation - BLAU, WERNER; COLEMAN, JONATHAN NESBIT (American Physical Society, 2005)
Novel polymer nanotube composites were fabricated by intercalating poly(vinylpyrrolidone) into Buckypaper from solution. This was carried out for both low (10k g?mol) and very high (1.3M g?mol) molecular weight polymers. Measurements of the polymer mass uptake as a function of time allowed the calculation of diffusion coefficients as 1.66?10?9 cm2?s and 3.08?10?12 cm2?s for the low and high molecular weight strands, respectively. Taking into account the molecular weights, comparison of these coefficients suggests that each polymer type undergoes a different mode of diffusion: normal diffusion for the 10k g?mol polymer, but reptation for the 1.3M g?mol polymer. This means that while the low weight polymer retains its randomly coiled conformation during diffusion and adsorption, the 1.3M g?mol molecule is forced to adopt an extended, high entropy state. These differences are reflected in the mechanical properties of the intercalated papers. While reinforcement was observed in all cases, modulus (increase ~?3.5 ) and strength (increase ~?6 ) enhancement occurred at lower polymer content for the longer chain polymer. However, the papers intercalated with the shorter chain molecules were much tougher (increase ~?25 ). This is consistent with the conformation scheme described above.
PUBLISHED PACS numbers: 81.07.De, 62.25.g, 81.05.Qk
Keywords: Physics